A head‐to‐head comparison between senolytic therapies, dasatinib plus quercetin and fisetin, indicates sex‐ and genotype‐specific differences in translationally relevant outcomes: Developing topics. (7th December 2020) - Garbarino, Valentina R; Tran, Sydney; Glassman, Jordan E; Kirkland, James L; Musi, Nicolas; Seshadri, Sudha; Orr, Miranda E
Abstract: Background: Senescent cells accumulate with advanced age and contribute to dysfunction and disability. We recently discovered that tau protein accumulation induces cellular senescence in Alzheimer's disease and other tauopathies, a group of brain diseases characterized by the deposition of tau protein (Musi et al., 2018). Treating mice with senolytics, drugs that specifically target senescent cells for their removal, reduced pathology and improved brain structure and function in tauopathy mice. Our initial study focused on dasatinib plus quercetin (D+Q). We now report results from directly comparing D+Q to fisetin (FIS) to determine differences in efficacy, toxicity, and sex and genotype as we work to translate this therapy to clinical studies. Method: Fourteen‐month old male and female wild type (WT) and tau transgenic (rTg4510) mice were treated intermittently (3 days on, 11 days off, for 6 cycles) with D+Q, FIS, or vehicle by oral gavage. Physical and behavioral outcomes were measured before and after treatment. Result: Both senolytic therapies significantly enhanced female rTg4510 mouse performance in the y‐maze (increased preference for novel arm (p = 0.00093 and p = 0.0015, D+Q and FIS, respectively); no treatment changes were noted in WT females or male mice. Pre‐ and post‐treatment comparisons of body weight revealed that D+Q uniquely increased body weight in female mice (WT: p=0.0005 and t: p = 0.024). Similarly, body length was increased by D+Q in WT (p= 0.0012) and rTg4510 (p= 0.0457) females, and WT males (p= 0.0481). Physical performance measures included run speed whereby D+Q increased WT female (p= 0.0002) and male (p=0.0267) velocity. FIS only affected WT males (p= 0.0022) but not females; and rTg4510 male (p=0.0015) but not female mice. Additional genotype, sex and treatment specific effects were observed in measures of frailty, grip strength, stride length, and nerve conduction. Our on‐going analyses of brain volumetry changes (MRI), axon integrity, transcriptomics, tau pathology, and inflammatory changes among the groups will provide mechanistic insights responsible for these behavioral phenotypes. Conclusion: Our study suggests that tailoring senolytic therapies to specific individuals based on sex and disease state may provide the most benefit as we translate this promising therapy to clinical use.